Induction of endotoxin tolerance in vivo inhibits activation of IRAK4 and increases negative regulators IRAK-M, SHIP-1, and A20 - Xiong, Yanbao (Society for Leukocyte Biology, 2011)
TLRs mediate host defense against microbial pathogens by eliciting production of inflammatory mediators and activating expression of MHC, adhesion, and costimulatory molecules. Endotoxin tolerance limits excessive TLR-driven inflammation during sepsis and reprograms macrophage responses to LPS, decreasing expression of proinflammatory cytokines without inhibiting anti-inflammatory and antimicrobial mediators. Molecular mechanisms of reprogramming of TLR4 signaling upon in vivo induction of endotoxin tolerance are incompletely understood. We used an in vivo model of endotoxin tolerance, whereby C57BL/6 mice were i.p.-inoculated with LPS or PBS, followed by in vitro challenge of peritoneal or splenic macrophages with LPS to examine activation of IRAK4 and expression of negative regulatory molecules. Administration of LPS in vivo-induced endotoxin tolerance in peritoneal and splenic macrophages, as evidenced by decreased degradation of IκBα, suppressed phosphorylation of p38 and reduced expression of TNF-α, IL-6, and KC mRNA upon in vitro LPS challenge. Macrophages from control and endotoxin-tolerant mice exhibited comparable TLR4 mRNA levels and similar expression of IL-1RA and IL-10 genes. Endotoxin tolerization in vivo blocked TLR4-driven IRAK4 phosphorylation and activation in macrophages, while increasing expression of IRAK-M, SHIP-1, A20 mRNA, and A20 protein. Thus, induction of endotoxin tolerance in vivo inhibits expression of proinflammatory mediators via impaired activation of IRAK4, p38, and NF-κB and increases expression of negative regulators of TLR4 pathways.